1997
DOI: 10.1038/386081a0
|View full text |Cite
|
Sign up to set email alerts
|

Osteopetrosis in mice lacking haematopoietic transcription factor PU.1

Abstract: Osteoclasts are multinucleated cells and the principal resorptive cells of bone. Although osteoclasts are of myeloid origin, the role of haematopoietic transcription factors in osteoclastogenesis has not been explored. Here we show that messenger RNA for the myeloid- and B-cell-specific transcription factor PU.1 progressively increases as marrow macrophages assume the osteoclast phenotype in vitro. The association between PU.1 and osteoclast differentiation was confirmed by demonstrating that PU.1 expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
326
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(339 citation statements)
references
References 19 publications
10
326
0
3
Order By: Relevance
“…90,100,101 Targeted disruption of the PU.1 gene also causes osteopetrosis and failure of the osteoclast differentiation. 117 In keeping with such a role, we found that the TRAP promoter can be transactivated in transfections of the macrophage cell line RAW264 by both PU.1 and Ets-2, and that the former factor acts through the conserved Ets element highlighted in Figure 2 (unpublished data). Immediately 5Ј of this element there is an E-box motif (CAnnTG), which we have found is a functional response element for the microphthalmia transcription factor (MiTF).…”
Section: Trap Expression In Osteoclastssupporting
confidence: 56%
“…90,100,101 Targeted disruption of the PU.1 gene also causes osteopetrosis and failure of the osteoclast differentiation. 117 In keeping with such a role, we found that the TRAP promoter can be transactivated in transfections of the macrophage cell line RAW264 by both PU.1 and Ets-2, and that the former factor acts through the conserved Ets element highlighted in Figure 2 (unpublished data). Immediately 5Ј of this element there is an E-box motif (CAnnTG), which we have found is a functional response element for the microphthalmia transcription factor (MiTF).…”
Section: Trap Expression In Osteoclastssupporting
confidence: 56%
“…The homozygous mutant embryos show a multilineage defect in the maturation of B and T lymphocytes, macrophages and neutrophils. The recent data which imply Spi-1/PU.1 in osteoclast development reinforce the major role of this transcription factor as a transcriptional regulator in the hematopoietic development (Tondravi et al, 1997). Moreover, the capital role of this gene may be further stressed by the recent ®nding that Spi-1/PU.1 interacts with RNA-binding proteins and binds RNAs in vitro (Hallier et al, 1996).…”
mentioning
confidence: 86%
“…These include the binding motif for activator protein 1 (AP1) which has shown to be involved in cell proliferation, differentiation and tumourigenesis, 44 upstream regulatory factor 1 (USF1) which has defined roles in regulation of genes expressed in the liver 45 and spleen focus forming virus proviral integration oncogene 1 (SPI1) which plays a role in the development of myeloid and b-lymphoid cells which are important during an immune response. 46 The functional importance of these TFs in regulation of CP expression should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%